Estimation of calcification detectability in breast tissues by means of the ultrasonic echo and shadow methods - FILIPCZYŃSKI, L.; ŁYPACEWICZ, G. (Archives of Acoustics, 1984)
Microcalcifications originate at an early stage of the breast cancer. Assuming their mechanical properties to be similar to those of the bone tissue, analysis was performed to find the smallest calcification size to be determined with ultrasonic echo and shadow methods. Taking into account the tissue interference background which has been determined experimentally, the electrical properties of the ultrasonograph and attenuation loss, basing on the theory of reflection from rigid and elastic spheres, the theoretical detectivity of calcifications in breasts could be estimated. It has been shown that at a frequency of 3 MHz spherical calcifications with the radii a > 0.15 mm situated at the depth R = 4 cm may be theoretically detected when using the echo method and a linear receiver. With the shadow method calcifications with radii greater than a = 1.5 mm are estimated to be detectable. This could be shown theoretically and experimentally using spheres made of plasticine.